Memahami Pengelolaan Risiko Usaha Dalam Syariah Entrepreneurship - Sry Wala Resky; Siradjuddin Siradjuddin; Irwan Misbach (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This article discusses about risk, risk management, and Islamic perspectives regarding opportunity administration. In this context, the article highlights the importance of understanding harm and how decision-making in financial management often involves thinking about confidence and vulnerability. The Islamic approach to managing life and risk reflects the belief that everything has been arranged by Allah SWT according to His plan. This leads to the idea that while risk cannot be avoided completely, we have the ability to reduce its impact through appropriate mitigation measures